Air Pollution Analysis of Preconstruction and Construction Phases in Sumatera Institute of Technology, South Lampung - Bambang Prasetio; Anggi Mardianto (Journal of Multidisciplinary Academic, 2020)
The Sumatra Institute of Technology (ITERA) is a state university located in Jati Agung, South Lampung Regency, Lampung Province. Although ITERA has a great potential for campus development in the next 20 years, there are a several challenges that ITERA must be designing. Here, air pollution from gasoline vehicles contributed 70% carbon monoxide (CO), 100% Plumb (Pb), 60% hydro carbon (HC) and 60% nitrogen oxide (NOX) in south Lampung area by Ministry of Environment (KLH) in 2010. Thus, air quality monitoring has a very important to determine polluted air over measurement location using comparing method based on Air Pollution Standard Index (ISPU). In this study, we identify and analyze pollutant concentrations in Sumatra Institute of Technology's over Pre-construction and Construction Phase and analyze the air pollution using the Ambien Air Quality Standards with ISPU in the Sumatra Institute of Technology. The data observation was conducted in 2017 while continuity of the air quality monitoring series at ITERA by adding more sampling points in 8 months (from March to October 2017). In addition, we use gas parameters from Sulphur dioxide (SO2), Nitrogen Dioxide (NO2), Oxidant (O3), Hydrocarbons (HC), PM10, Dust (TSP) which is refers to PP RI No.41 1999 concerning National Ambient Air Quality Standards.